Therapeutic targets by traditional Chinese medicine for ischemia-reperfusion injury induced apoptosis on cardiovascular and cerebrovascular diseases - Cheng, Xiuli; Hu, Jin; Liu, Xiaofeng; Tibenda, Jonnea Japhet; Wang, Xiaobo; Zhao, Qipeng (Frontiers in Pharmacology, 2022)
Traditional Chinese medicine (TCM) has a significant role in treating and preventing disease in humans. Ischemic heart disease (IHD) and ischemic cerebrovascular disease (CVD) are two types of diseases with different clinical manifestations that occur with high prevalence and incidence. In recent years, it has been reported that many TCMs have beneficial effects on ischemic diseases through multiple targets and pathways, especially the inhibition of apoptosis, which is the key target for TCM to treat cerebral ischemia and myocardial ischemia. This review provides a comprehensive summary of the mechanisms of various TCMs in the treatment of ischemic cardiovascular and cerebrovascular diseases through anti-apoptotic targets and pathways. Furthermore, correlative molecular mechanisms have been analyzed. Clinical investigations into elucidating the pharmacodynamic substance basis of TCM and their potential quality markers are still lacking, which should be further explored in the future. Overall, TCM has effectively treated ischemic cardio-cerebrovascular diseases by inhibiting apoptosis.